2008
DOI: 10.1111/j.1467-9922.2007.00438.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of German Word Order in Tutored Learners: A Cross‐Sectional Study in a Wider Theoretical Context

Abstract: This article presents the results from a cross-sectional study that tests predictions of processability theory (PT) regarding the acquisition of German word order. Spontaneous production data were elicited from 21 tutored second language learners of German who are native speakers of English. Each learner engaged in a 45-min informal conversation with a native speaker of German. The conversations were transcribed, analyzed, and implicationally scaled with respect to stages in the acquisition of German word orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…In the research field, the minimal number of contexts considered necessary to claim that a structure has emerged varies among researchers, ranging from one (Glahn et al, 2001) to three (Dulay & Burt, 1974;Zhang, 2005), four (Jansen, 2008;Meisel et al, 1981;Pienemann, 1998;Zhang, 2004), and even five (Andersen, 1978;Pienemann, 1998). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the research field, the minimal number of contexts considered necessary to claim that a structure has emerged varies among researchers, ranging from one (Glahn et al, 2001) to three (Dulay & Burt, 1974;Zhang, 2005), four (Jansen, 2008;Meisel et al, 1981;Pienemann, 1998;Zhang, 2004), and even five (Andersen, 1978;Pienemann, 1998). …”
Section: Discussionmentioning
confidence: 99%
“…Relying on Levelt's (1989) model of language production, PT describes the cumulative nature of unification points in a universal hierarchy of processability (see Pienemann, 1998Pienemann, , 2005 In PT, research on syntactic development has mainly focused on the development of word order regularities of various languages, including L2 German and L2 Swedish (for German : Boss, 1996;Clahsen, 1984;Clahsen, Meisel, & Pienemann, 1983;Ellis, 1989;Jansen, 2008;MeerholzHärle & Tschirner, 2001;Meisel et al, 1981;Pienemann, 1984Pienemann, , 1989for Swedish: Glahn et al, 2001;Håkansson, 2001;Håkansson & Norrby, 2007Philipsson, 2007;Pienemann & Håkansson, 1999;Rahkonen & Håkansson, 2008;Schönström, 2010). Different empirical studies have reported developmental sequences that are generally consistent with the processability hierarchy (see Table 1).…”
Section: Subordinate Clauses In L2 German and L2 Swedishmentioning
confidence: 99%
“…Learning settings affect the rate of learning and the overall accuracy of L2 production, with instructed learners in both foreign and second language settings progressing faster and being more accurate than naturalistic learners (e.g. Sato, 1990;Ellis, 1989;Jansen, 2008;Jia and Fuse, 2007).…”
Section: L2 Morphological Developmentmentioning
confidence: 99%
“…Pienemann and his colleagues have conducted numerous observational studies designed to assess the validity of TH. The studies that provide support for TH include the following: Felix (), Pienemann (, , , ), Boss (), Mansouri and Duffy (), Jansen (), Ellis (, ), Y. Zhang (), Gao (), and Wang (). They have shown that learners must progress from one processing stage to the next; that learners cannot skip stages; that instruction is only effective if it aims at stage X+1 and not X+2 or higher; that the progress of learners can be plotted on an implicational scale in a stepwise progression from least to most complex processing stage; and that if a learner can produce features at say Stage 4, he or she, implicationally, can also produce features at the three preceding stages.…”
Section: The Th As a Corollary Of Ptmentioning
confidence: 99%